Governance Reform of Sunan Gunung Djati State Islamic University through Risk-Based Budgeting - Prima Sari Putri (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper presents a policy analysis regarding the suboptimal integration and implementation of risk management comprehensively into the business processes and strategic decision-making of the State Religious College Public Service Agency (PTKN BLU) Sunan Gunung Djati State Islamic University, which directly hinders the improvement of the effectiveness of institutional governance control. The background to this issue is the disconnection between the high flexibility of BLU financial management and a weak internal control framework, exacerbated by the failure of internal regulations to bind risk to resource allocation. The writing method uses a qualitative-normative approach with public policy analysis, supported by a study of regulatory literature (Government Regulations, Ministerial Regulations) and governance theory (Enterprise Risk Management, Agency Theory) as well as an evaluation of policy alternatives using William N. Dunn's Scoring Theory. The results and discussion indicate that the main root of the problem is the weakness of formal policies that fail to make risk documents a mandatory prerequisite in the preparation of Business Plans and Budgets (RBA). The conclusion confirms that this problem is a structural weakness in governance. Therefore, the policy recommendation given is the Issuance of the Chancellor's Regulation on Risk-Based Performance and Budgeting Management, which requires every budget proposal to include an allocation of critical risk mitigation costs, in order to achieve optimal accountability and efficiency of BLU resources.